A Study of Supply Chain Strategy for Achieving Sustainable Transport Near National Park, Jerantut, Pahang, Malaysia - Mohd Sayuti Hassan; Siti Fairuz Mohd Radzi; Farehah Wahid; Saidatulakmal Mohd; Zikri Muhammad; Jumadil Saputra (International Journal of Supply Chain Management, 2020)
Bus service is the most practical sustainable transport solution for National Park. Unfortunately, there are various kinds of difficulties that prevent sustainable transport from being perfectly running, which are basically from two birthplaces, the people and the facilities. Of these, the current investigation is conducted to study the supply chain strategy for achieving sustainable transport at National Park, Jerantut, Pahang Malaysia. This quantitative study conducted by using a survey questionnaire to different groups, i.e., local community and National Park visitors. The data analyzed using the descriptive statistics analysis, which consist of frequency, percentage, mean and standard deviation. Also, this study uses graphical descriptive analysis. The results of the analysis show that the car is the most favourable method of transport followed by motorcycle. The reasons are not solely because of the lack of bus service. However, both local and tourist feel that they are more accessible, more comfortable and faster than the public bus. Thus, this study suggested that public transport facilities must be upgraded with better roads and better bus stops. Payment methods and tickets’ price is merely not a big issue for National Park. For promoting a sustainability issue, the National Park required more enhancements, not just the bus, the roads around also must be facilitated with more eco-friendly infrastructures to promote walking and cycling.Keywords— Supply Chain Strategy, Sustainable Transport, National Park, Tourist